The effect of cigarettes price on youth smoking behavior / Mohd Syukri Ali Omar - Ali Omar, Mohd Syukri (2014)
Youth and smoking is become a common scene that we can see on Malaysia, where it seen for government as a social problems and also increase the government revenue as well, where based on SEATCA report from 2005 till 2011 government revenue are 892 857 143 and 1 645 569 620 US Dollar respectively (Tobacco Tax, 2014). Even though it give an good revenue but it also give an bad impact towards the social and health problems for developing countries such Malaysia, where based on past research youth smoking is particularly acute problem in Malaysia, where as many as 60% of young males from lower socio-economic are smoker (Hana Ross, Nabila A .M Al-Sanadat, 2007). Thus the objective of this study is to study the relation of cigarettes price and implication of increasing cigarettes price towards the youth smoking behaviour.